Sleep patterns and its relation to lifestyle habits: a study of secondary high school students in Sharjah, United Arab Emirates - Amna Salam Al-Wandi; Sarra Ibrahim Shorbagi (AIMS Press, 2020)
Objectives: Sleep is a fundamental element in the growth and development of adolescents. Sleep undergoes significant changes during adolescence due to physiological and environmental factors. It has been scientifically shown that the required sleep duration in adolescence is more than 8 hours per day. The aim of this study is to understand sleep patterns and sleep-wake cycle of Sharjah adolescents, and identify lifestyle habits affecting those sleep patterns, and to assess the prevalence of sleep problems. Methods: The study was a cross-sectional survey of 519 high-school students, ages 14-21 years, in Sharjah city, United Arab Emirates. It was conducted using a self-filled questionnaire that included questions about demographic data, sleep and lifestyle habits and sleep problems of adolescents. Results: The mean age of our sample was 16.24. Most students (64.5%) were reported to sleep between 5 and 8 hours on school nights. The average time to go to bed on weekdays was 11:25 PM. The average time to wake up on weekdays was 6:12 AM. Frequent arousals with difficulty getting back to sleep was the most encountered sleep problem among our sample. Conclusion: A large proportion of adolescents in our study had insufficient sleep duration and suffer from some sleep disturbances. Smoking was found to be associated with sleep as non-smokers obtained longer sleep durations. There was no association between physical activity or usage of electrical devices and sleep. Therefore, it is necessary to intervene by organizing awareness programs to improve sleep patterns among adolescent students.